Performance Analysis of Updraft-Type Gasifier with Coconut Shell as Fuel - Katrian Ambawa Prawira; Sukmawaty; Amuddin, (J-AGENT (Journal of Agricultural Engineering and Technology), 2024)
Coconut shell is one of biomass that has an abundant source among us. But in most time are neglected and thrown away although it has a lot of benefits. One of its potential is to be a source of alternative energy. In this research, coconut shells are converted into combustible gas or syngas through gasification process by an updraft-type gasifier. The purpose of this research is to analyze the performance of the gasifier to generate heat with two different sizes of coconut shell as the fuel. The used coconut shell size are ± 3×3 cm (P1) and ± 5×5 cm (P2). The air supply used in this research is 7,13 m/s, or equivalent to 866,72 l/min. The method used in this research is an experimental one, then descriptively explained followed by data shown in charts. Heat that generated inside the reactor of P1 and P2 by average for 50 minutes are 413,6 °C and 420,9 °C. While the detected heat at the burner throughout the combustible gas generation are 375,7 °C for P1 and 396,3 °C for P2. The test for thermal efficiency by a water-boiling method is 2.22% for P1 and 2.43% for P2. While for the gasification efficiency simulation rate number are 55% for P1 and 65% for P2.